Interest in screening examinations among cancer patients - Humeniuk, Ewa; Dąbska, Olga; Pawlikowska-Łagód, Katarzyna; Goś, Anna; Matuska, Małgorzata (Nursing in the 21st Century, 2017)
INTEREST IN SCREENING EXAMINATIONS AMONG CANCER PATIENTSAim. To determine the influence of socio-demographic variables on attendance rate at screening examinations in cancer patients.Material and methods. The research group comprised of 100 cancer patients. The method applied in the research was a diagnostic survey. The research instrument was the authors‘ own questionnaire specially compiled to measure cancer patients‘ interest in screening examinations. The research material was analysed with the statistical packet STATISTICA 12 and Microsoft Office Excel software. Significance level was assumed at p